The Effect Of Hook Type (Type J, Kirby And Cyrcle) On Longline Catches (Mini Long Line) In The Teluk Pambang, Subdistrict Bantan, District Bengkalis, Province Of Riau - Muhamad Farhan; Nofrizal '; Isnaniah ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on 28 June to 5 July 2013 in the village of Bay Pambang Bengkalis Riau Province. The purpose of this study was to determine the effect of hook type (Type J, Kirby and Crycle) on long line catches (mini long line). The method used in this study is the experimental method. The results are presented in tables and histograms were analyzed using one way ANOVA formula. Based on the research it can be concluded that the type of hook J, Kirby and Cyrcel get the value of the average value of 2.77; 4.57 and 3.75. Where hook Cyrcel Kirby and more effective than the hook type A (Standard), from One Way Anova test hypotheses (Analisysisi of Variance) is 0089 less than the value of α = 0.05 level (p-value <α) gives the rate of fishing is not significantly different.Keywords : Long Line, Hook, Catch